The Interrelations of Genre in Traditional Cambodian Music and Theatre - Billeri, Francesca (European Journal of Musicology, 2022)
This article examines the interrelation and adaptation of musical and extramusical song features among the Cambodian genres of phleng kar (wedding music), phleng arak (music for arak spirits), lkhaon yiikee and lkhaon bassac (sung-danced theatre genres). It aims to discuss the concept of genre classification from the emic perspective of the Cambodian practitioners showing how they talk and think about their music; and to explore the kinds of culture-specific markers employed by Khmer musicians to distinguish their genres. Through selected case studies I show the interrelation of songs sharing the same title with different tunes; songs with same title and similar tunes; and songs with a different title but similar tunes. To these case studies I then applied music transcriptions and analysed musical and extramusical parameters to consider the exchange of musical features and performance analysis to consider the ritual context. This study shows how classification and categorization of genres, even when genres overlap, reflect sociocultural aspects and are attached to a set of musical and extramusical components.